Courting disaster: How diversification rate affects fitness under risk. (23rd December 2014) - Ratcliff, William C.; Hawthorne, Peter; Libby, Eric
<x xml:space="preserve">Abstract</x> Life is full of risk. To deal with this uncertainty, many organisms have evolved bet‐hedging strategies that spread risk through phenotypic diversification. These rates of diversification can vary by orders of magnitude in different species. Here we examine how key characteristics of risk and organismal ecology affect the fitness consequences of variation in diversification rate. We find that rapid diversification is strongly favored when the risk faced has a wide spatial extent, with a single disaster affecting a large fraction of the population. This advantage is especially great in small populations subject to frequent disaster. In contrast, when risk is correlated through time, slow diversification is favored because it allows adaptive tracking of disasters that tend to occur in series. Naturally evolved diversification mechanisms in diverse organisms facing a broad array of environmental risks largely support these results. The theory presented in this article provides a testable ecological hypothesis to explain the prevalence of slow stochastic switching among microbes and rapid, within‐clutch diversification strategies among plants and animals.